The Italian public health response during the pandemic emergency: from qualitative data to the “performance index” of care provided by Spoleto Hospital - Caroselli, Silvia; Roselli, Martina; Germani, Aldo; Fabiani, Marco; Micolonghi, Caterina; Visco, Vincenzo; Raffa, Salvatore; Mancini, Rita; Petrucci, Simona; Cardone, Alexander; Rossi, Orietta; Banchieri, Giorgio; et al. (Frontiers in Public Health, 2025)
BackgroundThe public health emergency was one of the most severe consequences of the COVID-19 pandemic outbreak, which occurred in successive waves since March 2020. In this scenario, the Hospital of Spoleto “San Matteo degli Infermi” (located in the Umbria region, Italy) became a COVID-19 referral center and therefore had to make organizational changes. This study aims to evaluate the quality of care provided during the pandemic and to explore what the hospital management should focus on.MethodsAn online survey related to ten topics across the five pandemic waves that took place in Italy from March 2020 to February 2022, was administered to the hospital unit referents. The qualitative responses collected were analyzed quantitatively using a recognized tool, called “Streetlight PRIority Swot” (SPRIS) system and based on a new and multilevel “strengths, weaknesses, opportunities, threats” (SWOT) matrix.ResultsIt was highlighted that the demand for continuity of care for patients and an increase in personal protective equipment were the issues that should have been the focus of the intervention after the first wave. Taking this into account, an improvement in performance was observed in the subsequent waves. Therefore, the results described a more than good quality of care provided among the hospital units, although with the need to improve the orthopedic services, emerged as the most critical area.Limitations, reasons for cautionDue to practical limitations, the study population was limited to the hospital unit referents. Future broader surveys may enrich the information from the hospital experience. The SPRIS system uses a general-to-specific approach which can lead to a complex outcome assessment. However, careful and continuous application supports the analytical validity and utility of this method.ConclusionThe analysis based on the SPRIS system showed the effective response of Spoleto Hospital after the first sudden wave for the following four pandemic waves, driven by the implementation of safety measures. The perspective adopted and the scenario tested can be seen as a starting point for an educational tool to monitor and evaluate health management strategies during emergency periods.